Pelaksanaan Pembacaan Al-Qur'an pada Upacara Pagi untuk Meningkatkan Hafalan Al-Qur'an Siswa di MTs Nur Ibrahimy Rantauprapat Kabupaten Labuhanbatu - Samaroh Hasibuan (Jurnal Zeniusi, 2026)
The implementation of tahfizhul Quran carried out by tahfizh teachers/tutors to students in memorizing juz 30, some apply the science of tajwid and makhrajul huruf, others do not use it so that the implementation of tahfizh tutors varies and the appointment of tutors is still not appropriate according to each person's expertise. The formulation of the research problem is how the implementation of tahfizhul Quran in the morning assembly, efforts made in improving students' memorization of the Quran and obstacles in improving the memorization of the Quran of students of the Nur Ibrahimy Private Middle School Rantauprapat Labuhanbatu Regency. This type of research is qualitative and uses descriptive methods. The informants of this research are students and teachers/mentors of tahfizh of the Nur Ibrahimy Private Middle School. The data collection instruments used are observation, interviews and documentation. The results of this study are the implementation of tahfizhul Quran is an additional program and the passing grade of students of the Nur Ibrahimy Private Middle School. The implementation of tahfizhul Quran is a form of awareness for the creation of a generation of hafidz-hafidzah who are able to memorize 1 juz and can improve students' memorization of the Quran and the tahfizhul Quran program can involve Madrasah students in the implementation of Musabaqah Tilawatil Quran  (MTQ)  at the Regency and Provincial levels. Efforts have included holding several Quran memorization competitions, awarding prizes, and providing additional time for extracurricular activities. Challenges include a lack of awareness of memorization, which considers it merely rote memorization, laziness, overwork, and inadequate mentoring.